WAJIB BELAJAR SEBAGAI PROGRAM YANG PRO RAKYAT DALAM MEWUJUDKAN AMANAT DALAM UUD NKRI TAHUN 1945 - Reza Aliza Sonia; Laila Rafendra; Bestari Assyva; Sakinah Devi Chandeni Hsb (Nalar: Journal of Pedagogy and Society, 2022)
Education is one of the most important things in national development, because education for the community will make people more advanced in their thinking. Advanced community thinking will form high-quality Human Resources (HR). The community also needs to know the importance of implementing compulsory education programs. Education is also inseparable from the role of government. The government prioritizes the importance of education for the entire community by improving education. Therefore, the government is obliged to fulfill the rights of every citizen in obtaining educational services in order to improve the quality of life of the Indonesian people. The government's concern in realizing a higher quality education begins with a quality education program. One of these policies is the existence of a 9-year compulsory education program. The government is also working to solve problems among the lower middle class people. The government is responsible for carrying out the education program for neglected children in the perspective of child protection laws.